Daily Text Messaging for Weight Control Among Racial and Ethnic Minority Women: Randomized Controlled Pilot Study - Steinberg, Dori M (JMIR Publications Inc., 2013)
BACKGROUND: Daily self-monitoring of diet and physical activity behaviors is a strong predictor of weight loss success. Text messaging holds promise as a viable self-monitoring modality, particularly among racial/ethnic minority populations. OBJECTIVE: This pilot study evaluated the feasibility of a text messaging intervention for weight loss among predominantly black women. METHODS: Fifty obese women were randomized to either a 6-month intervention using a fully automated system that included daily text messages for self-monitoring tailored behavioral goals (eg, 10,000 steps per day, no sugary drinks) along with brief feedback and tips (n=26) or to an education control arm (n=24). Weight was objectively measured at baseline and at 6 months. Adherence was defined as the proportion of text messages received in response to self-monitoring prompts. RESULTS: The average daily text messaging adherence rate was 49% (SD 27.9) with 85% (22/26) texting self-monitored behavioral goals 2 or more days per week. Approximately 70% (16/23) strongly agreed that daily texting was easy and helpful and 76% (16/21) felt the frequency of texting was appropriate. At 6 months, the intervention arm lost a mean of 1.27 kg (SD 6.51), and the control arm gained a mean of 1.14 kg (SD 2.53; mean difference –2.41 kg, 95% CI –5.22 to 0.39; P=.09). There was a trend toward greater text messaging adherence being associated with greater percent weight loss (r=–.36; P=.08), but this did not reach statistical significance. There was no significant association between goal attainment and text messaging adherence and no significant predictors of adherence. CONCLUSIONS: Given the increasing penetration of mobile devices, text messaging may be a useful self-monitoring tool for weight control, particularly among populations most in need of intervention. TRIAL REGISTRATION: Clinicaltrials.gov: NCT00939081; http://clinicaltrials.gov/show/NCT00939081 (Archived by WebCite at http://www.webcitation.org/6KiIIcnk1).